Design of Augmented Reality-Based Food Chain Learning Media for Grade V Elementary School Students - Alfia Dwi Handayani; Cita Dewi Pebriyana; Daniel Ahmad Gymanstiar; Indriani Nur Amanah; Rohma Milya Utami (Journal of Software Engineering, Information and Communication Technology (SEICT), 2023)
This study aims to produce a design of science learning media for grade 5 elementary school students regarding the food chain using an application made and based on Augmented Reality (AR). Multimedia Development Life Cycle (MDLC) is the method used in this study which consists of six stages, namely concept, design, material collecting, assembly, testing, and distribution. The subjects of this study were 5th grade elementary school students. Data collection techniques based on literature and literature. The software we use is Unity to create 2D or 3D objects by entering marker images into the vuforia engine database. After the application is built and tested on an android device, blackbox testing is carried out to assess software requirements and specifications. This design produces interactive learning media that is equipped with materials and supported by AR technology. The results of this study indicate that AR technology in grade 5 elementary school science learning media can be designed with more attractive and interactive visuals.